Chapter Uniting past and present: Sicily as a locus of identity between Greece and Rome - Fialho, Maria (Studi e saggi, 2022)
Basing on the accounts of Thucydides and Plutarch, the paper analyses the way Sicily and the proposed Athenian expedition to Sicily, as a strategic bridge to advance over Carthage, define Nicias and Alcibiades, and what they represent: old Athens, comprised of experienced rulers and devoted, thoughtful citizens, who retreat, aware of the madness and threat of disaster that will lead to the ruinous outcome of the civil war. Forced to join the expedition, Nicias, as the embodiment of this polis, will stay until the end, in a campaign with which he does not agree, trying to save his fellow citizens. Alcibiades together with what he represents are fighting fiercely for the realisation of a megalomaniacal dream that will bring fortune and power for their own advantage. While Nicias accepts the command out of duty and imitation, Alcibiades yearns for it. In this background, Sicily and Carthage, waving from afar with their wealth and promise of power, constitute the stimulus for action that ultimately destroys an Athens close to defeat. On the other hand, in the young Roman republic, Sicily and Carthage offer natural encouragement of the conquest and submission of their power, as an imperative of the logic of expansion, affirmation and survival of Rome as a nascent power. It is the generation of the old Roman nobility that claims Carthago delenda est.